Penerapan Fungsi Manajemen Dalam Pengelolaan Panti Asuhan Peduli Anak Yatim Palembang - Alan; Anang Walian (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Application of Management Functions in the Management of the Orphanage Caring for Orphans in Palembang". The function of management is to make it easier to achieve the goals of an activity. The problems are, 1) how to implement the management function in managing Peduli Anak care. 2) inhibiting and supporting factors in managing the orphanage that cares for orphans in Palembang. The aim of the research is to determine the application of management functions in managing the activities and resources of the orphanage caring for orphans in Palembang as well as the inhibiting and supporting factors in managing the orphanage. This type of research is descriptive qualitative field research. Data collection techniques include observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. Based on the results of research in orphanages that care for orphans using George R. Terry's theory in the application of management functions including planning, management of human resources and activities that are running well and there are still plans that are still in process, then organizing and placing tasks in the orphanage. care, direction in carrying out tasks, up to evaluation after carrying out program activities and development activities in the orphanage environment, up to the supporting factors and obstacles that exist in the process of managing the orphanage which come from internal such as existing resources and external factors come from from donors and the surrounding community in assisting the process of managing the orphanage. Up to the supporting factors and obstacles that exist in the process of managing the orphanage, which come from internal such as existing resources and external factors come from donors and the surrounding community in helping the process of managing the Palembang Care for Orphans orphanage